Pre-Extubation Ultrasound Measurement of In Situ Cuffed Endotracheal Tube Laryngeal Air Column Width Difference: Single-Center Pilot Study of Relationship With Post-Extubation Stridor in Subjects Younger Than 5 Years Old - Burton, Luke; Loberger, Jeremy; Baker, Mark; Prabhakaran, Priya; Bhargava, Vidit (Pediatric critical care medicine, 2024)
Post-extubation stridor (PES) is difficult to predict before extubation. We therefore evaluated the potential diagnostic performance of pre-extubation laryngeal air column width difference (LACWD) measurement, as assessed by intensivist-performed point-of-care laryngeal ultrasound, in relation to clinically important PES. Prospective observational cohort study. Single quaternary care PICU (July 19, 2021, to October 31, 2022). Included subjects were younger than 5 years old, intubated with a cuffed endotracheal tube, requiring invasive mechanical ventilation for greater than 24 hours, and nearing extubation. Subjects at high risk for supraglottic airway obstruction were excluded. Laryngeal ultrasound with measurement of laryngeal air column width with the endotracheal tube cuff inflated and deflated. Clinically important PES was defined as a high-pitched inspiratory respiratory noise suspected to be from a subglottic focus necessitating received medical intervention or reintubation. Among 53 enrolled subjects, 18 of 53 (34%) experienced PES and three of 53 (6%) were reintubated because of severe subglottic upper airway obstruction. Median LACWD was significantly lower in the stridor group compared with the nonstridor group (∆ 0.41 mm; 95% CI, 0.37-0.48; p < 0.001). The area under the receiver operating characteristic curve for LACWD as a diagnosis of PES was 0.94 (95% CI, 0.89-1.00; p < 0.001). The LACWD cutoff for PES was less than or equal to 0.47 mm, which yielded a diagnostic sensitivity of 91.4% and specificity of 88.9%. In this population, the pre-to-post-test change in probability of PES for LACWD less than or equal to 0.47 mm is 0.34 to 0.81. Pre-extubation LACWD is a novel, noninvasive assessment that can be performed and interpreted by the intensivist at the bedside. There is, however, diagnostic uncertainty in the use of this measurement for identifying those at-risk of PES and larger validation studies are needed.